Seroprevalence of antibodies against SARS-CoV-2 in the school community in Campo Grande, state of Mato Grosso do Sul, Brazil, October 2021–November 2022 - Stutz, Claudia; Alcantara, Daniel Maximo Correa; Santos, Camila Maria dos; Torres, Jaire Marinho; Rodrigues, Rudielle; Marcon, Glaucia Elisete Barbosa; Ferreira, Eduardo de Castro; Sarti, Elaine Cristina Fernandes Baez; Oliveira, Thiago Fernandes de; Mendes, Flavia Maria Lins; Lemos, Everton Ferreira; Demarchi, Luiz Henrique Ferraz; et al. (Frontiers in Immunology, 2024)
With the reopening of schools, during the COVID-19 pandemic, it was imperative to understand the role of students and educational professionals in the propagation process of SARS-CoV-2. We determined the seroprevalence of SARS-CoV-2 anti-nucleocapsid antibodies in the school community in Campo Grande, the capital and most populous city of Mato Grosso do Sul state (Brazil), and evaluated its association with sex, level of schooling and school type. The survey was carried out in 20 public and private schools in the urban region of Campo Grande using the TR DPP® COVID-19 IgM/IgG kit from the Immunobiological Technology Institute (Biomanguinhos). The testing was carried out in three periods: October to December/2021; March to July/2022 and August to November/2022. Students aged 6-17 years, enrolled in primary to secondary education, and professionals of different ages and roles participated. During the first testing period, 162 participants were seropositive for IgM and/or IgG anti-nucleocapsid-SARS-CoV-2 antibodies, with an estimated seroprevalence of 19.6%, using Bayesian multilevel regression. In the 2 nd period, 251 participants were seropositive (estimated seroprevalence of 34.6%), while in 3 rd period, 393 participants were seroconverted (estimated seroprevalence of 56.7%). In 2022, there was an increase in the seroconversion rate compared to that in 2021. The most frequently described acute manifestations in the three periods were fever, headache, sore throat, and runny nose. In terms of the demographic profile, there was no predominance of seropositivity between the sexes, although women represented approximately 70% of the study population. There were also no differences between education degrees and school staff. The results made it possible to evaluate the extent of SARS-CoV-2 transmission in the school community through immunity developed against the virus, in addition to providing information about COVID-19 symptoms in children, adolescents and adults.